Bioplastics from Wheat Gluten - แก้วตาทิพย์ แก้วตา (KKU Science Journal, 2013)
The accumulation of synthetic plastic wastes in nature has become a worldwide environmental problem. One partial solution to this problem is to produce and use bioplastics. Wheat gluten is an interesting raw material for the development of bioplastics, because of its low cost, availability in large quantities and biodegradability. In the presence of appropriate plasticizers, wheat gluten can be prepared using common thermoplastic processing. Wheat gluten is composed of many types of amino acids. However, cystine is the amino acid that plays an important role in bioplastics from wheat gluten. This is because SH groups can form disulfide (SS) bonds or crosslink between protein chains. The degree of crosslinking affects the quality of the final product. There are many factors that can influence the crosslinking such as the temperature during processing, the type of plasticizer and other additives. It is therefore necessary to control the extent of protein crosslinking because protein crosslinking plays a key role in the properties of the bioplastics from wheat gluten.